English Teachers’ Strategies To Motivate Students To Learn English At Madrasah Aliyah In Blitar - Siti Ngaisah; Ekka Zahra Puspita Dewi; Salma Hira; Intan Susana; Zuraida, Zuraida (CV. ULIL ALBAB CORP, 2025)
This study adopts a descriptive qualitative approach to explore the strategies employed by teachers to motivate students at madrasah aliyah in learning English, as well as how these strategies are applied in a madrasah aliyah located in Blitar. Data were collected through interviews with several English teachers and through direct classroom observations. The interview data were analyzed using a structured process involving transcription, familiarization, coding, theme identification, and reporting, as outlined by Darlington and Scott (2002). The findings revealed four key themes related to motivational strategies: creating a relaxed classroom environment, recognizing students' individual characteristics, connecting the learning process to real-life situations, and utilizing more creative teaching methods. This research offers valuable insights for both current and prospective educators in developing effective approaches to increase motivation among senior high school students in learning English.